Using neutralizing routines to reduce problem behaviors. - Horner, R H (1997)
Establishing operations can alter problem behaviors by changing the momentary value of reinforcers associated with those problem behaviors. If establishing operations (EOs) precede the presentation of discriminative stimuli (SDs) for problem behaviors, it may be possible to introduce neutralizing routines that both reduce the value of reinforcers associated with problem behaviors and decrease the occurrence of problem behaviors. The present study examined this logic with 3 adolescents with severe intellectual disabilities. Initial functional analyses indicated that problem behaviors were motivated by either escape or tangible items. Functional assessment interviews identified possible establishing operations that were associated with the occurrence of problem behavior and indicated that these establishing operations occurred over 1 hr before presentation of the SD for problem behaviors. We used an alternating treatments design to examine problem behaviors during instruction under four conditions: EO + SD, SD only, EO only, and neither SD nor EO. For all 3 participants, problem behaviors occurred almost exclusively during the EO + SD condition. A further analysis compared the EO + SD condition when neutralizing routines were embedded between the EO and the SD. Results from an ABAB reversal design supported the effectiveness of neutralizing routines to reduce these problem behaviors. Applied and theoretical implications are discussed.